Neuralized family member NEURL1 is a ubiquitin ligase for the cGMP-specific phosphodiesterase 9A - Taal, Kati; Sepp, Mari (Scientific reports, 2019)
Neuralized functions as a positive regulator of the Notch pathway by promoting ubiquitination of Notch ligands via its E3 ligase activity, resulting in their efficient endocytosis and signaling. Using a yeast two-hybrid screen, we have identified a cGMP-hydrolysing phosphodiesterase, PDE9A, as a novel interactor and substrate of Neuralized E3 ubiquitin protein ligase 1 (NEURL1). We confirmed this interaction with co-immunoprecipitation experiments and show that both Neuralized Homology Repeat domains of NEURL1 can interact with PDE9A. We also demonstrate that NEURL1 can promote polyubiquitination of PDE9A that leads to its proteasome-mediated degradation mainly via lysine residue K27 of ubiquitin. Our results suggest that NEURL1 acts as a novel regulator of protein levels of PDE9A.
Gesehen am 17.02.2020